(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2014)
The purpose of this paper is to study social security benefits for disability - disability retirement and sickness benefit, according to the prevailing doctrinal understanding - from the perspective of Social Security, understood as a plexus of fundamental human rights, of the second generation (art. 6), guaranteed by the Federal Constitution in its own chapter (arts. 201 and 202), founded on the constitutional pillar of human dignity (art. 1, III) and with a view to building a society of solidarity (art. 1, III). 6), guaranteed by the Federal Constitution in its own chapter (arts. 201 and 202), based on the constitutional pillar of the dignity of the human person (art. 1, III) and with a view to building a society based on solidarity (art. 3, I) and the good of all (art. 3, IV). As such, and in order to achieve maximum effectiveness and practical applicability (art. 5, §§ 1 and 2 of the FC), we will demonstrate the existence of fungibility between disability benefits, innovating by including in this list the benefit of accident aid of any kind, ontologically linked to the first two mentioned above due to the common social contingency (incapacity to work) caused by the triggering social events. At the end, we will analyze the consequences of this characteristic in the production of judicial protection when resolving conflicts presented before the Judiciary.